ANALISIS PENDIDIKAN SPIRITUAL DAN EMOSIONAL PASANGAN PERNIKAHAN DINI DI DESA RABESEN BESUK PERSPEKTIF JALALUDDIN RUMI - Asuroh, Lailatul; Adnan Q, Abu Yazid; Hidayatul H, Hawa’ (Jurnal Al-Fatih, 2025)
This research aims to analyze the spiritual and emotional dynamics experienced by early marriage couples in Rabesen Besuk Village, as well as reviewing this phenomenon through the Sufistic perspective of Jalaluddin Rumi. The background to this research is based on the widespread practice of early marriage in rural areas which often creates various psychological and spiritual challenges in household life. The method used in this research is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews and documentation. The main informants in this research were couples who married at an early age and local community leaders. The results of the research show that couples in early marriage experience emotional stress in the form of anxiety, domestic conflict, and immaturity in decision making. However, on the other hand, there is also a process of searching for meaning and spiritual maturity that develops along with the dynamics of married life. In Jalaluddin Rumi's perspective, this emotional experience is part of a spiritual journey towards self-purification and Divine love. Love, patience and suffering are seen not as obstacles, but as paths to finding identity and closeness to God. This research concludes that early marriage, although full of challenges, has transformative potential if lived with deep spiritual awareness as taught by Jalaluddin Rumi. Therefore, spiritual and emotional development is an important key in accompanying young couples who marry at an early age.